Sublethal Toxicity of Organophosphate Pesticides and its Effect on Hematology Parameter, Histopatology Hematopoietic Organ of Silver Rasbora (Rasbora argyrotaenia) - Lailatul - Lutfiyah (Airlangga University, 2020)
Pesticides are pollutants that are found in rice fields and rivers. Pesticides that are often used by farmers in Indonesia in eradicating insects are organophosphate insecticides, where they can eradicate insects that are very toxic to fish due to strong neurotoxic substances that inhibit AchE (Acetylcholinesterase) activity. The research aims to examine the effect of organophosphate pesticides on hematology and histopathology of hematopoietic organs in silver rasbora fish. The research method used is an experimental method with a CRD. The parameters observed were hematology and histopathology hematopoietic organ (liver and kidney). The results of this study showed a hematological change in silver rasbora fish where there was a decrease in total erythrocytes (0,59±0,004) and hemoglobin (2,5±0,1) while total leukocytes increased (245,35±15,78). Also, there are differential changes in leukocytes, namely an increased in the number of monocytes (5±1) and neutrophils (24±3), but lymphocytes have decreased in number (72±1). The Histopathology of the fish liver also can found in this research, those damages that are found are erythrocyte infiltration, necrosis picnosis, and karyolysis. Histopathology of fish kidney also can found cloudy sweling, necrosis karyolysis and tubular necrosis.